The Influence of Slope, Rock Characteristics and Meteorological Data to Landslide: A Case Study in The Northernmost Sumatra, Indonesia - Idris, Mochammad V.; Muksin, Umar; Syukri, Muhammad (UIR PRESS, 2024)
Landslides are natural disasters that can be caused by high rainfall intensity. Aceh Besar Regency has been hit by landslides 40 times from 2014 to 2023. Aceh Besar Regency serves as an economic connecting route from other cities to the provincial capital of Aceh, Banda Aceh. Therefore, when landslides occur in that area, it will disrupt the economic stability and logistic distribution to other regions. The weighted overlay method maps landslide-prone areas in Aceh Besar Regency. This research aims to create a map of landslide-prone areas in Aceh Besar Regency based on parameters causing landslides, namely slope inclination, rainfall, rock type, soil type, and land cover. The research findings indicate that almost the entire region of Aceh Besar has a moderate to high potential for landslide disasters. The main factor causing landslides in Aceh Besar is its topography, which is dominated by mountains and hills, and the moderate to very high rainfall intensity. The landslide-prone disaster map is validated by landslide incidents recorded by BPBD Aceh Besar from 2014 to 2023, showing results that align with the historical data. This map can be used by relevant authorities and the general public to undertake landslide disaster mitigation in Aceh Besar Regency.